Spectrum sensing-focused cognitive radio network for 5G revolution - Ali, Farhan; Yigang, He (Frontiers in Environmental Science, 2023)
The cognitive radio network (CRN), an instrumental part of the next generation of wireless communication systems, is mainly dependent on spectrum sensing to function properly. The radio spectrum can help in clean energy transition and load capacity factors by providing more efficient and accurate spectrum utilization. By using it, the amount of spectrum that is used for communication can be optimized, which can reduce the amount of energy consumed by the network. Additionally, 5G radio spectrum sensing can be used to identify and classify different types of signals, which can help reduce the amount of interference in the network and improve the efficiency of energy utilization. It can also allow for the digitization of clean energy infrastructure and facilitate better decision-making processes that take into account environmental impacts while optimizing energy use because of its efficient characteristics like non-linearity, detection, scalability, robustness, generalization, non-stationary in wireless environments, dynamic entity, the weighted sum of gaussian functions centered at specific frequencies, robust against noise and interference. It can adapt to noise and interference by adjusting its parameters, and this allows it to accurately distinguish between primary and secondary users in the wireless spectrum that’s why Radial Basis Function is a popular choice for spectrum sensing in 5G networks. RBFN can work better in 5G spectrum sensing for better signal classification, dynamic adaptation, fast detection, faster decision-making, and improved noise and interference reduction. one of the most sought-after goals in the field of wireless research is the creation of spectrum-sensing technology that is dependable and intelligent. Because multilayer learning approaches are inappropriate for dealing with time-series data due to the higher misclassification rate and inherent computational complexity. To address this, the study proposed the Radial Basis Function Networks (RBFNs) that learn temporal aspects from the spectral data and make use of additional environmental statistics such as frequency, efficiency, energy, spectrum allocation, distance, and duty cycle time are considered as environmental data that may be used to fine-tune sensor performance. The scheme is simulated with real-time parameters and results are quite promising in terms of the evaluation parameters.